Clinical features and seasonality of parechovirus infection in an Asian subtropical city, Hong Kong. - Grace P K Chiang; Zigui Chen; Martin C W Chan; Simon H M Lee; Angela K Kwok; Apple C M Yeung; E Anthony S Nelson; Kam Lun Hon; Ting Fan Leung; Paul K S Chan (PLoS ONE, 2017)
Background The epidemiology of human parechovirus (HPeV) in Asia remains obscure. We elucidated the prevalence, seasonality, type distribution and clinical presentation of HPeV among children in Hong Kong. Methods A 24-month prospective study to detect HPeV in children ≤36 months hospitalized for acute viral illnesses. Results 2.3% of the 3911 children examined had HPeV infection, with most (87.5%) concentrated in September-January (autumn-winter). 81.3% were HPeV1 and 12.5% were HPeV4, while HPeV3 was rare (2.5%). HPeV was a probable cause of the disease in 47.7% (42/88), mostly self-limiting including acute gastroenteritis, upper respiratory tract infection and maculopapular rash. A neonate developed severe sepsis-like illness with HPeV3 as the only pathogen detected. A high proportion (60.0%) of children coinfected with HPeV and other respiratory virus(es) had acute bronchiolitis or pneumonia. Six children with HPeV coinfections developed convulsion / pallid attack. Most rash illnesses exhibited a generalized maculopapular pattern involving the trunk and limbs, and were more likely associated with HPeV4 compared to other syndrome groups (36.4% vs. 3.1%, p = 0.011). Conclusions In Hong Kong, HPeV exhibits a clear seasonality (autumn-winter) and was found in a small proportion (2.3%) of young children (≤36 months) admitted with features of acute viral illnesses. The clinical presentation ranged from mild gastroenteritis, upper respiratory tract infection and febrile rash to convulsion and severe sepsis-like illness. HPeV3, which is reported to associate with more severe disease in neonates, is rare in Hong Kong. HPeV coinfection might associate with convulsion and aggravate other respiratory tract infections.